El principio de seguridad jurídica en la jurisprudencia del tribunal constitucional: caso huatuco - Torres Quiróz, Julio Bettino (2017)
The objective of this research was to determine whether, in the immediate application of the constitutional precedent "Huatuco" to the amparo proceedings in the judicial branch or Constitutional Court, the principle of legal certainty established in the case law of the Court Constitutional has been violated. The research has been qualitative, not experimental, with descriptive, interpretive and prospective, applied to a sample conformed by a sentence of the Constitutional Court that established a binding precedent, and by a set of sentences of the same maximum organ of interpretation of the Constitution, With respect to institutions of legal certainty and binding constitutional precedent; Whose institutions still do not have a positive legal regulation within the legal system. The investigation allowed concluding that: 1) The principle of legal certainty established in the jurisprudential line of the Constitutional Court has been violated through the immediate application of the binding precedent "Huatuco" to the amparo proceedings in process